Die staat van toegevoegde waarde as komponent van finansiele verslaggewing in die RSA - A. P. Du Plessis; D. S. Joubert (South African Journal of Business Management, 1991)
The value added statement as component of financial reporting in the RSA The value added statement was developed due to a need for more understandable financial information for the uninformed user of financial statements. Although not required by the Companies Act, since 1977 numerous South African companies have included a value added statement in their financial reports. The question can, however, be asked whether the inclusion of a statement of value added in financial reports will not put financial information at the disposal of a larger group of existing and potential users of financial statements. In such a case the inclusion of the statement should be made compulsory and the contents be standardized. During a study of the reasons for the publication and the presentation of the information of this statement by South African companies, it was found that companies probably publish this statement for the annual competitions for financial statements. The information contents of the statement is therefore disregarded.